2015
DOI: 10.2174/1381612820666141014142557
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species in Pathogenesis of Atherosclerosis

Abstract: The volume of publications on the role of reactive oxygen species (ROS) in biological processes has been increasing exponentially over the last decades. ROS in large amounts clearly have detrimental effects on cell physiology, whereas low concentrations of ROS are permanently produced in cells and play a role as signaling molecules. An imbalance in ROS production and defense mechanisms can lead to pathological vascular remodeling, atherosclerosis being among them. The aim of this review is to examine different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 194 publications
(220 reference statements)
1
52
0
1
Order By: Relevance
“…Oxidative damage plays a critical role in this process830. Gene transfer of catalase can reduce ROS production and ameliorate vascular remodeling, as is found31.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Oxidative damage plays a critical role in this process830. Gene transfer of catalase can reduce ROS production and ameliorate vascular remodeling, as is found31.…”
Section: Discussionmentioning
confidence: 95%
“…Although present agents control blood pressure well, the nontoxic agents for vasoprotection are weakly effective but still necessary. It has been proved that excessive reactive oxygen species (ROS) are closely related to vascular pathologies8. Vascular wall is particularly vulnerable to oxidative damage.…”
mentioning
confidence: 99%
“…Reactive oxygen species (ROS) plays a critical role in the development of atherosclerosis [25][26][27]. It was demonstrated that a significant amount of ROS was produced spontaneously from ox-LDL at clinically relevant concentrations, and was involved in the action of ox-LDL on human umbilical vein endothelial cells [28,29], bone marrow (BM) stem cells [30], vascular smooth muscle cells [31], monocytes [32], macrophage [33] and foam cells [34].…”
Section: Introductionmentioning
confidence: 99%
“…The most common cause of CVD is atherosclerosis, which involves inflammation in the vessel wall, as explained above [8]. It is frequently caused by the infiltration of low density lipoproteins (LDL) the endothelium through a wall damage, once trapped in the sub endothelium, the LDL became more prone forming the oxidized LDL (oxLDL) [9, 10].…”
Section: Introductionmentioning
confidence: 99%